TEACHING PRACTICE GUADIANCE BY USNING THE APPRECIABLE MODEL’S METHOD TO ENHANCE THE TEACHING SKILL UPON SCIENTIFIC SUBJECT TOWARD TEACHER’S CANDIDATE AS AN EFFORT TO RAISE ITS QUALITY - SUDARISMAN, SUCIATI (Prodi Pendidikan Biologi FKIP UNS, 2005)
Study on implementation of teachning practice guidance by using the appreciable model?s method has been carried out in oerder to enhance the teaching skill of teacher?s andidate in teaching the scientific subject. The model applied by the candidates during teaching was created by the supervisors. The study it self was carried out during the student?s practice of teaching in 3 junior high school, supervised by 3 lecturer and 3 senior teachers. The candidates were then asked to make the review toward that method and disscuss it with the supervisor. The results indicated that appreciable model?s method could be as alternative method used by the candidate an supervisor during the guidance of teacher?s candidate. It was showed by the raising of the candidate?s skill in making the teaching materials preparation, and also the teaching sill respectively. Key Words : teaching practice guadiancce, appreciable model?s method